ANALISIS DAN PERANCANGAN SISTEM INFORMASI KNOWLEDGE MANAGEMENT SYSTEM DI PT METEOR INOVASI DIGITAL - Jaya Susilo, Kevin; Arijanto, Rudy (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2025)
Technology has become a crucial element in both individual and industrial life, not only facilitating daily tasks but also serving as a pillar in facing challenges and business competition. This research aims to develop a user-friendly knowledge management system application at PT Meteor Inovasi Digital, with the goal of replacing conventional approaches to knowledge storage with a more efficient application system. The research methodology includes planning, analysis, design, and implementation phases. Planning involves identifying existing problems, while analysis relates to information and system requirements. Design focuses on interface modeling, database structuring, and data flow to facilitate development. Implementation includes the development and deployment of the application, ensuring resource availability in accordance with the design outcomes. Data from questionnaire surveys, completed by 10 staff members of PT Meteor Inovasi Digital, provide insights into user responses to the developed system. The conclusion highlights the development of an information system to maintain and enhance the efficiency of knowledge utilization in the company. The designed system aligns with the company's needs, following the steps of a knowledge management roadmap to create an effective and efficient ecosystem for storing and utilizing knowledge. It also supports the migration plan to a knowledge management system from the conventional methods still in use.